Tadeusz Maciejewski, Historia administracji, 2002 - Janicka, Danuta (Czasopismo Prawno-Historyczne, 2003)
Recenzja: Tadeusz Maciejewski, Historia administracji, Wydawnictwo C.H. Beck, Warszawa 2002, ss. 321.